Isotope Effects in the Electrodeposition of Ag and Pd - Pyyhtiä Kimmo; Peljo Pekka (Elsevier BV, 2025)
The influence of solvent and its isotope in electrochemical deposition of silver and palladium on pencil graphite from H2O, D2O and MeCN was examined via cyclic voltammetry, chronoamperometry and SEM imaging. The evaluation of the nucleation process was done by comparing the current transients to Scharifker–Hills model of nucleation and the process for all samples was deemed to be progressive and mostly under diffusion control. Kinetic parameters were extracted from I/t curves by curve fitting to Heerman–Tarallo model and it was found that for silver and palladium electrodeposition the isotope of the solvent has a noticeable effect on nucleation rate constant with only a limited effect on the number density of nucleation sites.